Nutritional characterization and biological activity of Opuntia ficus-indica (L.) Mill. fruit - Silva, M.A. (2019)
Introduction: Nowadays, consumers demand for foods that contain compounds with enhanced nutritional quality. Opuntia ficus-indica (L.) Mill belongs to the Cactaceae family and is a tropical or subtropical plant that grows wild in the arid and semi-arid regions of the world. However, its nutritional and bioactive potential remains to be exploited. The aim of this study was to evaluate the nutritional composition and biological activity of O. ficus-indica fruit pulp. Materials and Methods: In 2017, the prickly pears were obtained at Herdade de Peliteiros (Silveiras, Montemor-o-Novo, Évora). Nutritional composition was determined according to the methods described by Albuquerque et al. (2016) (1). The energy value and available carbohydrates were calculated (2, 3). Antioxidant activity of prickly pear was determined using two different methods (2,2-diphenyl-1-picryl-hydrazyl (DPPH•) and ferric reduction power (FRAP)) (4). Moreover, total phenolic and total flavonoids contents were also assessed by spectrophotometric methodologies (4). Results: With the results obtained, it was possible to verify that water is the main constituent of the pulp (83%), the energy value was 59 kcal/245 kJ per 100 g of edible portion and total dietary fibre was 4.8 g/100 g of edible portion. The total phenolics content for the analysed prickly pear pulp was 19.8 ± 0.78 mg gallic acid equivalents/g, while the total flavonoid content was 1.70 ± 0.08 mg epicatechin equivalents/g. Regarding the antioxidant activity evaluation, the results obtained for the two different analytical methods applied, were 17.12 ± 0.71 mg/mL and 46.6 ± 1.99 mg Trolox eq./g for DPPH• and FRAP assays, respectively. Discussion and Conclusions: Based on the results obtained for the analysed prickly pear pulp, it is possible to conclude that it is a good source of bioactive compounds and could contribute to the intake of natural antioxidants. It is a fruit with nutritional interest and its use in human diet can bring potential health benefits to consumers.